An Analysis Of Problem-Solving Skills in the Activity of Analyzing Short Stories of Grade VIII Students at SMPN 4 Cina, Bone Regency - Dusreni, Andi St. Aisyah; Usman, Usman (ppjbsip, 2025)
This study aims to describe the problem-solving skills of eighth-grade students at SMPN 4 Cina, Bone Regency, in analyzing short stories. The study employed a descriptive quantitative method with a survey designThe analysis was guided by Polya’s four problem-solving. Data were collected through essay-based tests developed from five selected short stories and validated by an Indonesian language teacher. The data were analyzed using descriptive statistical techniques based on Polya’s four indicators: identifying problems, formulating problems, analyzing problems, and drawing conclusions. The results show that students’ problem-solving skills fall into the moderately skilled category, with an average score of 77.3. The highest achievements were found in stories with explicit and realistic conflicts, while symbolic and implicit texts led to lower performance. These findings indicate that the clarity and complexity of narrative structures significantly influence students’ analytical and reflective abilities in short-story analysis. Abstrak Penelitian ini bertujuan untuk mendeskripsikan keterampilan memecahkan masalah siswa kelas VIII SMPN 4 Cina Kabupaten Bone dalam menelaah cerpen. Penelitian ini menggunakan metode kuantitatif deskriptif dengan desain survei. Data dikumpulkan melalui tes esai berbasis lima cerpen yang telah divalidasi oleh guru bahasa Indonesia. Data dianalisis menggunakan teknik statistik deskriptif berdasarkan empat indikator Polya, yaitu mengidentifikasi masalah, merumuskan masalah, menganalisis masalah, dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa keterampilan memecahkan masalah siswa berada pada kategori cukup terampil dengan rata-rata skor 77,3. Pencapaian tertinggi ditunjukkan pada cerpen dengan konflik yang eksplisit dan realistis, sedangkan cerpen yang bersifat simbolik menghasilkan capaian yang lebih rendah. Temuan ini mengindikasikan bahwa kejelasan dan kompleksitas struktur naratif berpengaruh signifikan terhadap kemampuan analitis dan reflektif siswa dalam menelaah cerpen.